2021
DOI: 10.21608/jsasj.2021.222731
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fertilization with Mineral NPK and Spraying with Nano NPK on Growth, Yield and Quality of Onion

Abstract: Two field experiments were conducted during 2018/2019 and 2019/2020 seasons at Shandaweel Agriculture Research Station, Sohag Governorate, to study the effect of different rates of mineral NPK fertilization under foliar application with Nano NPK, on vegetative growth, yield and quality of onion. Split plot design with three replicates was used. Mineral NPK fertilization rates occupied the main plots (100% NPK, 75% NPK, 50% NPK and 25% NPK), whereas Nano NPK spraying rates (control, 2 L/fed, 4 L/fed and 6 L/fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Nitrogen (N) is an essential mineral nutrient required in high concentrations for wheat growth, productivity, and quality [ 43 , 44 ]. Accordingly, among the agricultural inputs, N fertilizer is a key concern.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen (N) is an essential mineral nutrient required in high concentrations for wheat growth, productivity, and quality [ 43 , 44 ]. Accordingly, among the agricultural inputs, N fertilizer is a key concern.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, the tomato yield was lower. Also, Ali et al, (2021) reported that application of 100 % of NPK on onion gave the highest values of plant height and total yield. Carricondo-Martínez et al, (2022) reported that conventional mineral fertigation management gave the highest yield of tomato, followed by vermicompost treatments at two different doses (3 and 9 kg/m), with no statistical differences.…”
Section: Effects Of Fertilization On Fruit Yield Characteristics: a T...mentioning
confidence: 99%
“…At 60 DAT treatments T6, T7, 78 and T9 were found to be statistically at par with T11. The agronomic qualities of the produce were enhanced by higher levels of nitrogen [11] and [13].…”
Section: Leaf Fresh Weight (G)mentioning
confidence: 99%